2017
DOI: 10.4172/2157-7579.1000428
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Gastrointestinal Nematodes Infections in Small Ruminants in Tullo District, Western Harerghe, Ethiopia

Abstract: A cross-sectional study was carried out in sheep and goats kept under extensive management system in Tullo district, Western Harerghe zone of Oromia Regional State, Ethiopia, during the period from November, 2013 to April, 2014. The main objectives of the study were to estimate the prevalence of nematode infection in small ruminants and to assess associated risk factors with its occurrence. A total of 384 fecal samples were collected from 168 sheep and 216 goats. The samples were examined using floatation tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
8
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 7 publications
7
8
3
Order By: Relevance
“…There were no statistically significant differences in the shedding of nematode eggs between male and female sheep ( Table 2 ). These results are in agreement with the findings of a study from Ethiopia [ 31 ] and Bangladesh [ 32 ]. In contrast, a significantly higher number of female than male goats had nematode eggs in their faeces.…”
Section: Discussionsupporting
confidence: 93%
“…There were no statistically significant differences in the shedding of nematode eggs between male and female sheep ( Table 2 ). These results are in agreement with the findings of a study from Ethiopia [ 31 ] and Bangladesh [ 32 ]. In contrast, a significantly higher number of female than male goats had nematode eggs in their faeces.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast to previous studies (Regassa et al, 2006;Tefera et al, 2009;Admasu and Nurlign, 2014) which reported relatively lower proportion of massive infection in sheep and goats, this study demonstrated that a higher proportion of sheep (60%) and goats (48.3%) examined were heavily infected. Consistent to the current finding, a higher proportion of massive infection has also been documented in other studies in the country (Abebe et al, 2010;Ahmed et al, 2017;Getachew et al, 2017). Observation of heavy intensity of infection in the present study may be attributed to lack of regular deworming practice in the farm and consequently increased contamination of grazing pasture with eggs excreted by infected animals.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, a high prevalence of GIN infection was recorded in both sheep (83.3%) and goats (87.9%) in KALHARI farm. This finding is higher than the prevalence reported by much of previous studies which ranges between 47.2 to 75.3% in sheep and 34.2 to 84.1% in goats in different parts of the country (Abebe et al, 2010;Admasu and Nurlign, 2014;Yimer and Birhan, 2016;Ahmed et al, 2017;Derso and Shime, 2017;Getachew et al, 2017). In contrast, higher prevalence than the present had been reported by other studies (Tefera et al, 2009;Aragaw and Gebreegziabher, 2014;Wondimu and Gutu, 2017).…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…In many parts of Ethiopia considerable amount of researches have been carried outby different researchers to investigate prevalence and intensity of nematode infection in small ruminants. The researches carried out around DebreZeit, ArsiNegele, Haramaya and Western Hararge by [18,19,20,21] showed prevalence of GI nematodes as being 86.7%, 69.01%, 88.8% and 50.8%respectively. In the district, the main form of agricultural practice is mixed (crop-livestock) production system where people mostly focus on crop production which leaves small area (marginal land, swampy and mountain) for grazing of animals.…”
Section: Introductionmentioning
confidence: 99%